Das Framework und die Erstsemesterstudierenden der Medizin: Ein Erfahrungsbericht aus der Universitätsbibliothek Würzburg - Blümig, Gabriele; Klein, Diana; Wolf, Simone (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2021)
This article describes the design of a new one-shot information literacy session for students of medicine in the first semester at the University Library Würzburg. After giving a short introduction into the threshold concept and the theoretical background of the Frameworks for Information Literacy for Higher Education (Framework) we focus on the content of the course in terms of frames, knowledge practices and dispositions. Finally we analyse the evaluation outcomes and show how we transformed the session into an e-learning-based course.